Effects of Charge Density on Photophysics and Aggregation Behavior of Anionic Fluorene-Arylene Conjugated Polyelectrolytes - Martelo, Liliana M. (2018)
Three anionic fluorene-based alternating conjugated polyelectrolytes (CPEs) have been synthesized that have 9,9-bis(4-phenoxy-butylsulfonate) fluorene-2,7-diyl and 1,4-phenylene (PBS-PFP), 4,4'-biphenylene (PBS-PFP2), or 4,4″-p-terphenylene (PBS-PFP3) groups, and the effect of the length of the oligophenylene spacer on their aggregation and photophysics has been studied. All form metastable dispersions in water, but can be solubilized using methanol, acetonitrile, or dioxane as cosolvents. This leads to increases in their emission intensities and blue shifts in fluorescence maxima due to break-up of aggregates. In addition, the emission maximum shifts to the blue and the loss of vibronic structure are observed when the number of phenylene rings is increased. Debsity Functional Theory (DFT) calculations suggest that this is due to increasing conformational flexibility as the number of phenylene rings increases. This is supported by increasing amplitude in the fast component in the fluorescence decay. The nonionic surfactant n-dodecylpentaoxyethylene glycol ether (C12E₅) also breaks up aggregates, as seen by changes in fluorescence intensity and maximum. However, the loss in vibrational structure is less pronounced in this case, possibly due to a more rigid environment in the mixed surfactant-CPE aggregates. Further information on the aggregates formed with C12E₅ was obtained by electrical conductivity measurements, which showed an initial increase in specific conductivity upon addition of surfactants, while at higher surfactant/CPE molar ratios a plateau was observed. The specific conductance in the plateau region decreased in the order PBS-PFP3 < PBS-PFP2 < PBS-PFP, in agreement with the change in charge density on the CPE. The reverse process of aggregate formation has been studied by injecting small volumes of solutions of CPEs dissolved at the molecular level in a good solvent system (50% methanol-water) into the poor solvent, water. Aggregation was monitored by changes in both fluorescence and light scattering. The rate of aggregation increases with hydrophobicity and concentration of sodium chloride but is only weakly dependent on temperature.